Review of Policing Insurgencies: Cops as Counterinsurgents - Sullivan, John P. (International Journal of Police Science, 2022)
Book: Policing Insurgencies: Cops as Counterinsurgents, ed. C. Christine Fair and Sumit Ganguly (Delhi: Oxford Academic, 2014), ISBN 9780198094883 (print), ISBN 9780199082896 (online), https://doi.org/10.1093/acprof:oso/9780198094883.001.0001.